Predicting Structural Consequences of Antibody Light Chain N-Glycosylation in AL Amyloidosis - Gareth J. Morgan; Zach Yung; Brian H. Spencer; Vaishali Sanchorawala; Tatiana Prokaeva (MDPI AG, 2024)
Background/Objectives: Antibody light chains form amyloid fibrils that lead to progressive tissue damage in amyloid light chain (AL) amyloidosis. The properties of each patient's unique light chain appear to determine its propensity to form amyloid. One factor is N-glycosylation, which is more frequent in amyloid-associated light chains than in light chains from the normal immune repertoire. However, the mechanisms underlying this association are unknown. Here, we investigate the frequency and position within the light chain sequence of the N-glycosylation sequence motif, or sequon. Methods: Monoclonal light chains from AL amyloidosis and multiple myeloma were identified from the AL-Base repository. Polyclonal light chains were obtained from the Observed Antibody Space resource. We compared the fraction of light chains from each group harboring an N-glycosylation sequon, and the positions of these sequons within the sequences. Results: Sequons are enriched among AL-associated light chains derived from a subset of precursor germline genes. Sequons are observed at multiple positions, which differ between the two types of light chains, κ and λ, but are similar between light chains from AL amyloidosis and multiple myeloma. Positions of sequons map to residues with surface-exposed sidechains that are compatible with the folded structures of light chains. Within the known structures of λ AL amyloid fibrils, many residues where sequons are observed are buried, inconsistent with N-glycosylation. Conclusions: There is no clear structural rationale for why N-glycosylation of κ light chains is associated with AL amyloidosis. A better understanding of the roles of N-glycosylation in AL amyloidosis is required before it can be used as a marker for disease risk.